The Death Penalty In Indonesia: A Theological Perspective of Law - Katarina Leba; Yohanes Endi; Balthasar Watunglawar; Fransesco Agnes Ranubaya (International Journal of Indonesian Philosophy & Theology, 2023)
This study aims to explore, analyze and describe the theological perspective on the death penalty and God's way of eradicating evil to answer whether the death penalty can be justified theologically. This research used a descriptive qualitative method. Through this literature review, data are collected and analyzed theologically. The study results found that crime and the death penalty are human products. Evil is the output or impact of human sin. God's works are always related to goodness and the best judgment of God's creations. Evil, including the death penalty, could not be justified because God did not want evil for His creation. Therefore, when humans fell into sin, God ceaselessly saved and converted humans as he sent His only begotten son, willing to die to atone for human sins or save them. In addition to the sacrifice of Jesus, God's way of eradicating evil is also: willingness to suffer, application of sank and rules, forgiveness, radical love, and following Jesus. Theologically, the death penalty is evil, so it cannot be accepted because, for Thomas Aquinas, all forms of the law might be placed in the context of the bonum commune, with the principle of “bonum est faciendum et prosequendum et malum vitandum.” God’s sincerity to suffering must be how humans convert and save fellow humans. Likewise, legal products must align with the goals of the common good and welfare. This research uses a qualitative method. The problem limitation in this article is regarding the legal theological perspective on the death penalty in Indonesia. The findings of this study show that the death penalty is undoubtedly contrary to Thomas Aquinas' moral-theological principle in which God seeks to save humanity, not destroy it.